Investigating the Level of Experience in Using More Effective Software Design Tools for Enhancing Security among Federal College of Education, Gidan Madi Staff and Students - Hajara Abdulkadir; Bello Alhaji Buhari; Abdulrahman Umar (PT. Delitekno Media Madiri, 2025)
Higher education institutions operate under strict regulations and standards to ensure compliance with data protection rules, safeguard sensitive information, and preserve the privacy of employees and students. This study evaluates the expertise of staff and students at the Federal College of Education, Gidan Madi, in employing software design tools to enhance security. Using a mixed-methods approach, the research involves a wide range of stakeholders, including academics, non-academics, and students. The findings reveal that software design tools significantly improve the institution's ability to detect and respond to security events. Participants highlighted the importance of data encryption, expressed confidence in their knowledge of the latest advancements in security tools, and rated institutional support for security measures as excellent. The study also identified gaps in network monitoring capabilities, which are critical for proactive security management. Based on these findings, the study recommends the implementation of advanced network monitoring tools to enhance security measures at the institution. These results are expected to benefit higher education stakeholders, IT administrators, and decision-makers responsible for designing and maintaining robust security systems. By addressing current challenges and improving expertise in using security tools, this research contributes to the broader goal of strengthening data protection in higher education institutions.